The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s42255-020-0178-9
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes influences bacterial tissue compartmentalisation in human obesity

Abstract: Visceral obesity is a key risk factor for type 2 diabetes (T2D). Whereas gut dysbiosis appears to be instrumental for this relationship, whether gut-associated signatures translocate to extra-intestinal tissues and how this affects host metabolism remain elusive. Here we provide a comparative analysis of the microbial profile found in plasma, liver and in three distinct adipose tissues of individuals with morbid obesity. We explored how these tissue microbial signatures vary between individuals with normoglyca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
164
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(200 citation statements)
references
References 43 publications
22
164
0
1
Order By: Relevance
“…This result is consistent changes in Enterococcaceae regulating insulin, since intermittent fasting lowers blood insulin and glucose and improved insulin sensitivity, coincident with a decreased relative abundance of Enterococcaceae in obese, diabetic, db/db mice [21]. Furthermore, while bacterial LPS has been shown to impair insulin clearance, we have recently shown that members of the Enterococcaceae family compartmentalize in the tissues of individuals with T2D, independently of obesity [22].…”
Section: Discussionsupporting
confidence: 78%
“…This result is consistent changes in Enterococcaceae regulating insulin, since intermittent fasting lowers blood insulin and glucose and improved insulin sensitivity, coincident with a decreased relative abundance of Enterococcaceae in obese, diabetic, db/db mice [21]. Furthermore, while bacterial LPS has been shown to impair insulin clearance, we have recently shown that members of the Enterococcaceae family compartmentalize in the tissues of individuals with T2D, independently of obesity [22].…”
Section: Discussionsupporting
confidence: 78%
“…Recent developments including multitechnical approaches [224] and more recently, contaminant-aware approaches [214,217] to evidence the existence of extra-intestinal bacteria and their relationship with metabolism point to the fact that one cannot simply repudiate the existence of tissue-specific bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas no differences in bacterial load were found within tissues between subjects with and without T2D, subjects without T2D displayed a significantly increased bacterial diversity in bacterial signature of mesenteric adipose tissue, pointing to a link between tissue-specific bacterial signature and glucose tolerance similar to observations of microbial diversity in gut microbiome studies. A specific strength of this study is the extensive inclusion of negative controls at each step of the preanalytical and experimental procedure accounting for operation field contamination at tissue collection, environmental contamination during tissue manipulation including air samples from surroundings and swab controls for used surfaces, as well as negative controls for DNA extraction, amplification, and sequencing, making it one of the first studies to present contamination-aware evidence of tissue-specific bacterial compartmentalization with a T2D extra-intestinal microbial signature, which was independent of obesity [214]. This evidence could further be expanded by recently published data from our group, where we succeeded in detecting adipose tissue borne living bacteria using catalyzed reporter deposition (CARD) -fluorescence in situ hybridization (FISH).…”
Section: Bacterial Presence In Remote Tissuesmentioning
confidence: 99%
“…Bacterial translocation and tissue microbiota in humans are subjects of intense debate since several years ago [ 18 , 22 , 23 , 24 , 25 ]. Although some authors hypothesize that adipose tissue microbiota may come from the intestine when leaky gut occurs, there is still no reliable evidence in CD.…”
Section: Introductionmentioning
confidence: 99%